RECENT CHANGES IN INFECTIOUS DISEASES IN EUROPEAN WILDLIFE - Yon, Lisa; Duff, J. Paul; Ågren, Erik O.; Erdélyi, Károly; Ferroglio, Ezio; Godfroid, Jacques; Hars, Jean; Hestvik, Gete; Horton, Daniel; Kuiken, Thijs; Lavazza, Antonio; Markowska-Daniel, Iwona; et al. (Journal of wildlife diseases, 2019)
Many infectious diseases originating from, or carried by, wildlife affect wildlife conservation and biodiversity, livestock health, or human health. We provide an update on changes in the epidemiology of 25 selected infectious, wildlife-related diseases in Europe (from 2010–16) that had an impact, or may have a future impact, on the health of wildlife, livestock, and humans. These pathogens were selected based on their: 1) identification in recent Europe-wide projects as important surveillance targets, 2) inclusion in European Union legislation as pathogens requiring obligatory surveillance, 3) presence in recent literature on wildlife-related diseases in Europe since 2010, 4) inclusion in key pathogen lists released by the Office International des Epizooties, 5) identification in conference presentations and informal discussions on a group email list by a European network of wildlife disease scientists from the European Wildlife Disease Association, or 6) identification as pathogens with changes in their epidemiology during 2010–16. The wildlife pathogens or diseases included in this review are: avian influenza virus, seal influenza virus, lagoviruses, rabies virus, bat lyssaviruses, filoviruses, canine distemper virus, morbilliviruses in aquatic mammals, bluetongue virus, West Nile virus, hantaviruses, Schmallenberg virus, Crimean-Congo hemorrhagic fever virus, African swine fever virus, amphibian ranavirus, hepatitis E virus, bovine tuberculosis (Mycobacterium bovis), tularemia (Francisella tularensis), brucellosis (Brucella spp.), salmonellosis (Salmonella spp.), Coxiella burnetii, chytridiomycosis, Echinococcus multilocularis, Leishmania infantum, and chronic wasting disease. Further work is needed to identify all of the key drivers of disease change and emergence, as they appear to be influencing the incidence and spread of these pathogens in Europe. We present a summary of these recent changes during 2010–16 to discuss possible commonalities and drivers of disease change and to identify directions for future work on wildlife-related diseases in Europe. Many of the pathogens are entering Europe from other continents while others are expanding their ranges inside and beyond Europe. Surveillance for these wildlife-related diseases at a continental scale is therefore important for planet-wide assessment, awareness of, and preparedness for the risks they may pose to wildlife, domestic animal, and human health.